Association of Aspartate Aminotransferase (AST) and Alanine Aminotransferase (ALT) with Mortality in Patients with Coronavirus Disease 2019 (COVID-19) in Fatmawati General Hospital: A Preliminary Data - Nikko Darnindro; M Ikhsan Mokoagow; Annela Manurung; Jerry Nasarudin; Elisabeth Yasmine Wardoyo; Anggraini Permata Sari; Aryan Yohanes Djojo; Martha Iskandar; Giri Aji; Radhiyatam Mardiyah; Nadya Magfira; Marina Epriliawati; Edi Mulyana; Arnold Harahap (The Indonesian Society for Digestive Endoscopy, 2020)
Background: COVID-19, caused by SARS-CoV-2 virus, is a novel disease that has not been previously identified. The disease may result in multiple organ impairment leading to death. Liver is also affected by this viral infection. This study aimed to investigate the association of aspartate aminotransferase (AST) and alanine aminotransferase (ALT) with mortality rate in these patients.Method: This is a retrospective cohort study of COVID-19 patients admitted in Fatmawati General Hospital during a period of March-April, 2020. Diagnosis of COVID-19 was established from real time Polymerase chain reaction (RT PCR). Association of AST and ALT levels with mortality was analyzed by using SPSS® version 16.0.Results: Forty-two patients were diagnosed as confirmed case of COVID-19, 52.3% of them were male. Mean age was 54.6±12 years. Median (IQR) value of AST and ALT levels were 55(48) U/L and 39(40) U/L, respectively. AST and ALT was elevated in 71.4% and 42.9%, respectively. Increased levels of AST and ALT 2 times above the upper normal limit (UNL), 2 times ULN, and 5 times ULN were found in 33.3% and 21.4%; 38.1% and 21.4%; 4.8% and 4.8%, respectively. Mortality was recorded in 45.1% of these confirmed cases, 50% occurred within 2 days of hospitalization. Higher mean value of AST is associated with an increased mortality risk (101 ± 147 U/L vs. 82.78 ± 173 U/L; p 0.032). Sub-analysis identified that abnormal AST 2 times above UNL has a higher mortality proportion compared with AST 2 times UNL and normal AST levels (62.5% vs. 50% vs. 16.7%; p 0.05). Mean value of ALT is not associated with mortality (p 0.479). Further sub-analysis found that in patients who succumbed to the disease, abnormal levels of AST and ALT is related to the time of death during hospitalization despite being statistically not significant.Conclusion: Mortality rate of COVID-19 in hospitalized patients remains high. Increased AST levels was significantly associated with higher mortality rate. This finding merit further investigation by incorporating larger sample size to discern the role of these factors’ contribution to mortality in COVID-19.